- GAMBARAN STATUS GIZI PENDONOR DARAH SUKARELA DI UDD PMI KABUPATEN BANYUMAS TAHUN 2022 - Yuli Astuti - (Jurnal Ilmiah Cerebral Medika, 2022)
ABSTRACTBackground: There is high public awareness to voluntarily donate blood at UDD PMI Banyumas Regency. This makes researchers to know the level of nutritional status of voluntary blood donors.Research Objectives: This study aims to determine the level of nutritional status of voluntary blood donors at UDD PMI, Banyumas Regency.Methods: The research design uses a quantitative descriptive. The research sample was 98 donors. The sampling technique uses accidental sampling.Results: The results showed that based on the characteristics of the donor's weight, it can be seen that the majority of donors have a weight category (60-85kg) of 56 people (57.1%), based on the characteristics of the donor's height, it can be seen that the majority of donors have a height of 160 -185 cm in 69 people (70.4%), based on the characteristics of the BMI category it can be seen that the majority of donors have a normal BMI of 41 people (41.8%).Conclusion: Body Mass Index results obtained for voluntary blood donors at UDD PMI Banyumas Regency with normal criteria were 41 people (41.8%).Keywords: Blood Donation, Nutritional Status